High‐Temperature Ultrafast Sintering: Exploiting a New Kinetic Region to Fabricate Porous Solid‐State Electrolyte Scaffolds. Issue 34 (19th July 2021) - Wang, Ruiliu; Dong, Qi; Wang, Chengwei; Hong, Min; Gao, Jinlong; Xie, Hua; Guo, Miao; Ping, Weiwei; Wang, Xizheng; He, Shuaiming; Luo, Jian; Hu, Liangbing
Abstract: Solid‐state batteries (SSBs) promise better safety and potentially higher energy density than the conventional liquid‐ or gel‐based ones. In practice, the implementation of SSBs often necessitates 3D porous scaffolds made by ceramic solid‐state electrolytes (SSEs). Herein, a general and facile method to sinter 3D porous scaffolds with a range of ceramic SSEs on various substrates at high temperature in seconds is reported. The high temperature enables rapid reactive sintering toward the desired crystalline phase and expedites the surface diffusion of grains for neck growth; meanwhile, the short sintering duration limits the coarsening, thus accurately controlling the degree of densification to preserve desired porous structures, as well as reducing the loss of volatile elements. As a proof‐of‐concept, a composite SSE with a good ionic conductivity (i.e., ≈1.9 × 10 −4 S cm −1 at room temperature) is demonstrated by integrating poly(ethylene oxide) with the 3D porous Li6.5 La3 Zr1.5 Ta0.5 O12 scaffold sintered by this method. This method opens a new door toward sintering a variety of ceramic‐SSE‐based 3D scaffolds for all‐solid‐state battery applications. Abstract : A facile, ultrafast, and general method to sinter 3D porous solid‐state electrolyte (SSE) scaffolds on various substrates is developed. The sintered porous SSE demonstrates desired crystallinity, adjustable porous structure, and high electrochemical performance. This method opens a new route toward constructing a range of 3D SSE scaffolds for all‐solid‐state battery applications.